Enoch Adeboye : father of nations - Bible-Davids, Rebecca (London: Biblos Publishers, 2009)
Powerful classic! author Pastor Rebecca Bible-Davids presents this fascinating biography of Pastor Enoch Adeboye, a modern day Apostle to the nations and the overseer of the Redeemed Christian Church of God. He overseers one the largest Christian Movements with over 200,000 pastors in over 140 nations of the world. in this classic biography, the author traces his life from the trials of his early life to his rise to the peak of excelllence in life and ministry
Includes bibliographical references and index.
opc 04/01/17
Loans
Keywords: Enoch Adeboye; Biographies